2011
DOI: 10.1097/sla.0b013e318237826b
|View full text |Cite
|
Sign up to set email alerts
|

The Short-term Outcomes of Conventional and Single-port Laparoscopic Surgery for Colorectal Cancer

Abstract: This study shows that SPLS is both safe and feasible in colorectal cancer, and that it has equivalent or better short-term outcomes than conventional laparoscopic surgery. Accordingly, the authors conclude that SPLS can be an alternative to conventional laparoscopic surgery for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 29 publications
7
91
0
Order By: Relevance
“…Kim et al [3] showed that postoperative recovery was faster in the SILC group in terms of shorter time duration before first flatus (SILC vs CLC; 2.5 ± 1.2 d vs 3.2 ± 1.8 d, P = 0.004), earlier initiation of free oral fluids (1.8 ± 2.2 d vs 2.6 ± 1.7 d, P = 0.000) and of a solid diet (4.2 ± 2.9 d vs 6.5 ± 2.7 d, P = 0.000), less frequent usage of parenteral narcotics (2.2 ± 3.2 times vs 3.5 ± 4.0 times, P = 0.029), and shorter hospital stay (9.6 ± 9.6 d vs 15.5 ± 9.8 d, P = 0.000) ( Table 3). With regard to oncologic clearance, 14 studies reported average lymph node harvest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [3] showed that postoperative recovery was faster in the SILC group in terms of shorter time duration before first flatus (SILC vs CLC; 2.5 ± 1.2 d vs 3.2 ± 1.8 d, P = 0.004), earlier initiation of free oral fluids (1.8 ± 2.2 d vs 2.6 ± 1.7 d, P = 0.000) and of a solid diet (4.2 ± 2.9 d vs 6.5 ± 2.7 d, P = 0.000), less frequent usage of parenteral narcotics (2.2 ± 3.2 times vs 3.5 ± 4.0 times, P = 0.029), and shorter hospital stay (9.6 ± 9.6 d vs 15.5 ± 9.8 d, P = 0.000) ( Table 3). With regard to oncologic clearance, 14 studies reported average lymph node harvest.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified one randomized contro lled trial and 13 cased-matched control or comparative studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In total, 1559 colorectal resections were included, 589 by SILC and 970 by CLC.…”
Section: Resultsmentioning
confidence: 99%
“…Single incision gastrectomy for gastric cancer or matched retrospective study, even though the number of sample size was limited (11)(12)(13)(14).…”
Section: Review Articlementioning
confidence: 99%
“…Various research has been undertaken to assess early results and complications of SPLC compared to MPLC. These studies have proven the feasibility and safety of the SPLC for benign and malignant colorectal diseases even in emergencies (1,6,(17)(18)(19)(20)(21). It has been shown that distinct benefits of SPLC over MPLC consist of using only one umbilical entry point with multiple incorporated working channels, reducing pain and complications like bleeding, hernia, tissue trauma, and improving the cosmesis (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%